Board and management gender diversity and financial performance of microfinance institutions - Michael Adusei; Samuel Yaw Akomea; Kwasi Poku (Cogent Business & Management, 2017)
We investigate board and management gender diversity issues in the microfinance setting with data (2010–2014) drawn from 494 microfinance institutions across 76 countries. We find that board gender diversity positively predicts management gender diversity. On the effects of board and management gender diversity on the financial performance of microfinance institutions (MFIs), we find that whereas board gender diversity is negatively and significantly related to MFI financial performance, management gender diversity is negatively but insignificantly related to MFI financial performance. We show that 50% or higher diversity in either board or management is the threshold at which gender diversity is productive to MFIs. However, danger exists that an MFI that combines 50% or higher female representation on its board with 50% or higher female representation on its management team is likely to experience a tumble in its financial performance. The overall effect of these outcomes is that the push for more female representation on boards and management teams of MFIs should be done with a lot of tact and circumspection.
Keywords: 650